ECOLOGICAL DESTRUCTION IN THE POEMS TIGER-TIGER REVISITED (2009), FOR A COMING EXTINCTION (1967), EXTINCTION OF MAN: NUCLEAR WINTER (2009) - Rangga Fajriya Tanamal; Kurnia Ningsih; An Fauzia Rozani Syafei (English Language and Literature, 2018)
This study is aimed to expose the issue about the ecological destruction which is done by people toward the nature and to know the contribution of poetic elements; irony, tone, and speaker in revealing the issue of ecological destruction. This analysis is related to the concept of eco-criticism by Garrard, Glotfelty, Michael P Cohen, and John Evelyn. The result of this analysis shows that the ecological destruction is done in two ways; exploitation and technological abuse.